Edutainment Methods in the Learning Process: Quickly, Fun and Satisfying - Zhu Feiyue (Three E Science Institute, 2022)
The spirit of edutainment learning is in the learning process that is fun, comfortable, and amazing and is in how the interaction between teachers and students is established with close, friendly, and harmonious communication like friends. That way students do not feel restricted, afraid and can interact freely and happily. The purpose of this study was to determine the effectiveness of the edutainment approach to learning. The research location is at the Tourism Middle School Academy in Makassar, Indonesia with a sample size of 31 students. The research process through Classroom Action Research (CAR) was carried out for one semester. The results of the evaluation show that through the edutainment approach, students prefer to learn more, and student achievement in learning has increased as seen from the percentage of success achieved reaching 57 percent, previously only 23 percent for learning to write and learning to read, the percentage of success was up to 62 percent previously 25 percent. The Edutainment approach is a variation in learning strategies that convey subject matter by combining question and answer methods with fun and creativity. The assessment of students must be more flexible, there must be variations in the assessment, for example, with written evaluations, singing and speaking.